Perception and practices of EFL teachers towards teaching socio- cultural contents for 10th graders at Le Huu Trac high school, Dak Lak province - Luong Hien Bao Thanh; Nguyen Thi Quynh Hoa (Tạp chí Khoa học và Công nghệ)
The 2018 General Education Program (GEP) has significantly reformed the Vietnamese education system. One of its requirements is for students to respect cultural diversity. This article aims at examining English as a Foreign Language (EFL) teachers’ perception and practices toward teaching socio-cultural contents (SCC) presented in the new textbook, “Tieng Anh 10 - Global Success”, for 10th graders. It employs qualitative methods with the support of quantitative information. The study applies a questionnaire, semi-structured interviews, classroom observations and teaching materials to collect data from seven teachers at Le Huu Trac (LHT) High School. The findings reveal that most teachers appreciate socio-cultural integrations (SCI) and agree that SCI does not prevent progress in terms of language accuracy. SCI’s motivational benefits and positive impacts on learners' language skills were approved. However, teachers devote little time and effort to SCI. The study also proposes several implications and suggestions.